2013
DOI: 10.1128/aem.03609-12
|View full text |Cite
|
Sign up to set email alerts
|

Direct Assessment of Metabolite Utilization by Pseudomonas aeruginosa during Growth on Artificial Sputum Medium

Abstract: bWe grew Pseudomonas aeruginosa in LB and artificial sputum medium (ASM) (filtered and unfiltered) and quantified metabolite utilization and excretion by nuclear magnetic resonance (NMR) spectroscopy (metabolic footprinting or extracellular metabolomics). Utilization rates were similar between media, but there were differences in excretion-e.g., acetate was produced only in unfiltered ASM.T he opportunistic pathogen Pseudomonas aeruginosa is the major cause of morbidity and mortality for cystic fibrosis (CF) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Despite a number of recent studies focused on adaptive changes in evolved populations of P. aeruginosa in environments designed to mimic CF sputum (60)(61)(62)(63)(64)(65), there remain significant gaps in knowledge about how genomic and phenotypic diversity impacts upon on interactions within populations and on community-level phenotypes. In our current study, we focused on understanding how the evolution and coexistence of multiple lineages of P. aeruginosa shape community functions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a number of recent studies focused on adaptive changes in evolved populations of P. aeruginosa in environments designed to mimic CF sputum (60)(61)(62)(63)(64)(65), there remain significant gaps in knowledge about how genomic and phenotypic diversity impacts upon on interactions within populations and on community-level phenotypes. In our current study, we focused on understanding how the evolution and coexistence of multiple lineages of P. aeruginosa shape community functions.…”
Section: Discussionmentioning
confidence: 99%
“…It may prove to be the case that tests using such designed media prove more relevant to clinical outcome than those using standard methods, but this will require correlations of in vitro results, clinical courses, and posttreatment cultures. This has not yet even been done with P. aeruginosa infections, although studies of growth and metabolism of that bacterium in these media have been performed (30,31). Of note, the two media tested in which A. fumigatus could grow appeared to make the isolates generally more susceptible to drug inhibition, although digested sputum medium made the isolates more resistant to killing.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al have also demonstrated that sputum amino acid concentrations correlate with the severity of CF lung disease [ 24 ]. Most CF pathogens grown in ASM show their normal characteristics, including specific gene expression, strong micro-colony formation, metabolite utilization, surface motility, evolutionary diversity and, most importantly, rigorous antibiotic resistance, which likely reflect the real pathological situation in the lung [ 20 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 ]. Thus, the accumulated evidence confirms the suitability of ASM for microbiological CF research.…”
Section: Discussionmentioning
confidence: 99%